Identifying Topics by Position - Lin, Chin-Yew; Hovy, Eduard (Fifth Conference on Applied Natural Language Processing, 1997)
This paper addresses the problem of identifying likely topics of texts by their position in the text. It describes the automated training and evaluation of an Optimal Position Policy, a method of locating the likely positions of topic-bearing sentences based on genre-specific regularities of discourse structure. This method can be used in applications such as information retrieval, routing, and text summarization.